A Pipeline for Natural Small Molecule Inhibitors of Endoplasmic Reticulum Stress - Correia da Silva, Daniela; Valentão, Patrícia; Andrade, Paula B.; Pereira, David M. (Frontiers in Pharmacology, 2022)
The homeostasis of eukaryotic cells is inseverable of that of the endoplasmic reticulum (ER). The main function of this organelle is the synthesis and folding of a significant portion of cellular proteins, while it is also the major calcium reservoir of the cell. Upon unresolved ER stress, a set of stress response signaling pathways that are collectively labeled as the unfolded protein response (UPR) is activated. Prolonged or intense activation of this molecular machinery may be deleterious. It is known that compromised ER homeostasis, and consequent UPR activation, characterizes the pathogenesis of neurodegenerative diseases. In an effort to discover new small molecules capable of countering ER stress, we subjected a panel of over 100 natural molecules to a battery of assays designed to evaluate several hallmarks of ER stress. The protective potential of these compounds against ER stress was evaluated at the levels of calcium homeostasis, key gene and protein expression, and levels of protein aggregation in fibroblasts. The most promising compounds were subsequently tested in neuronal cells. This framework resulted in the identification of several bioactive molecules capable of countering ER stress and deleterious events associated to it. Delphinidin stands out as the most promising candidate against neurodegeneration. This compound significantly inhibited the expression of UPR biomarkers, and displayed a strong potential to inhibit protein aggregation in the two aforementioned cell models. Our results indicate that natural products may be a valuable resource in the development of an effective therapeutic strategy against ER stress-related diseases.